ChemInform Abstract: Sodium Tungstate: The First Application as Non‐oxidative Catalyst in Organic Synthesis. Issue 40 (30th September 2014) - Khodabakhshi, Saeed; Baghernejad, Mojtaba
Abstract A convenient synthesis of some pyranocoumarins (IV) via a one‐pot, three‐component condensation is described.